The Raman spectra of serine and 3,3-dideutero-serine in aqueous solution - Jarmelo, S. (2007)
The Raman spectra of serine [[alpha]-amino-[beta]-hydroxypropionic acid; HOCH2CH(NH3)+COO-] and 3,3-dideutero-serine [HOCD2CH(NH3)+COO-] in aqueous solution were studied in the range 4000-300 cm-1. The data obtained for the deuterated compound are novel and provide compelling evidence that previously reported assignments for the undeuterated amino acid should be revised.